Non-Western Theories in International Relations Education and Research: The Case of Turkey/Turkish Academia - Okur, Mehmet Akif; Aytekin, Cavit Emre (CENTER FOREIGN POLICY & PEACE RESEARCH, 2023)
This study examines the usage of non-Western theories in research and education by International Relations (IR) scholars in Turkey. Our primary purpose is to understand the level of engagement with the non-Western IR debate, with its prospects and variations, in Turkish academia, and to evaluate the familiarity of Turkish IR scholars from different schools with non-Western IR theories. Relevant data were obtained from a questionnaire with 47 items designed to let participants, consisting of 116 academicians at IR departments from 57 Turkish Universities, provide their teaching experiences, views, and perceptions concerning non-Western IR Theory. While our findings based on this data confirm the literature on the scarcity of non-Western theories in Turkish IR scholarship, we have also furthered it with many details. Firstly, according to the findings, respondents who study and teach IR Theory at Turkish universities think that the IR theories of Western origin dominating the literature are not universal or objective in terms of their function as interpreters of IR issues. But interestingly, those considerations direct scholars to Western critical IR Theory schools rather than non-Western theories. The other key conclusion of this study confirms our expectations. The thoughts, concepts and theories emanating from the Turkish-Islamic world have much more recognition than other non-Western IR theories among Turkish IR scholars.
Keywords: Non-Western IR theory; Turkish International Relations; International Relations education; theoretical preferences; survey; AMERICAN SOCIAL-SCIENCE; RELATIONS IR; DISCIPLINE; PERIPHERY; DOMINANCE; DIVERSITY; PEDAGOGY; International Relations